Evaluation of Level Transmitter Performance Through Calibration Data in the Instrument Maintenance Unit of PLTGU Cilego - Muhammad Rizki; Diyajeng Luluk Karlina; Yudi Nugraha (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study evaluates the consistency of transmitter level performance through calibration data obtained from the Instrumentation Maintenance Unit of the Cilegon PLTGU. The purpose of this study is to determine the accuracy, linearity, and stability of transmitter output against standard reference values. Qualitative methods were used, including direct observation, interviews, and literature studies to support the analysis of calibration procedures. Calibration data from the Masoneilan 12420-51 and Yokogawa EJA210E transmitters were analyzed using a comparative approach between normal and abnormal calibration results. Classification was based on the difference between the actual output and the 4–20 mA standard signal, with a tolerance limit of ±0.25% in accordance with ISA and IEC calibration standards. The results of the study show that the Level-3 Deaerator Storage Tank transmitter operates within the normal range, with excellent linearity and accuracy, while the Flash ST Tank Level transmitter shows minor deviations outside the tolerance limit, categorized as abnormal. These deviations suggest the potential for drift or zero shift influenced by environmental factors and aging. This study concludes that periodic calibration is necessary to maintain tranmitter performance reliability and ensure accurate signal transmission in the automatic control system at the Cilegon PLTGU facility.